Ocrelizumab – a monoclonal antibody – in the treatment of adult patients with multiple sclerosis: a systematic review - D. L. Klabukova; M. E. Holownia-Voloskova; M. V. Davydovskaya; T. N. Ermolaeva; K. I. Polyakova; A. G. Fisun; K. A. Kokushkin (Фармакоэкономика)
Aim: To analyze the efficacy, safety and pharmacoeconomic aspects of using ocrelizumab in adult patients with relapsing/remitting multiple sclerosis (R/R MS).Materials and Methods. We used the commonly accepted PICo(S) questionnaire with the following specifics: the population – patients with R/R MS; the intervention – ocrelizumab; the comparators – all disease-modifying treatments for MS; the outcomes – the annualized relapse rate, confirmed disability progression, MRI results, quality-adjusted years of survival (QALYs), adverse events, and other clinical outcomes. The search for the relevant information was conducted in 2018 by using the embase, PubMed, Cochrane and eLibrary.ru databases and the «ocrelizumab» AND «multiple sclerosis» keywords. The levels of evidence and conclusiveness of the cited studies were also assessed.Results. Treatments with ocrelizumab resulted in a lower rate of disease progression as compared with interferon β -1a. As evidenced by a randomized clinical trial, the annualized relapse rate estimated after 96 weeks was lower with ocrelizumab than that with interferon β-1a (0.16 vs. 0.29, 47% decrease, p<0.001). For most secondary end points, patients on ocrelizumab showed better outcomes than those on interferon β-1a. In the ocrelizumab group, the most common adverse events were caused by reactions to the drug infusion, nasopharyngitis, upper respiratory and urinary tract infections, and headaches. No cases of progressive multifocal leukoencephalopathy have been reported so far. ocrelizumab is more clinically effective than the first-line disease-modifying therapies; this conclusion also refers to patients with the aggressive (highly active) form of MS. ocrelizumab showed the efficacy similar to the second-line disease-modifying therapies, but it had a more favorable safety profile. The pharmacoeconomic indices showed that using ocrelizumab had a positive impact on the budget in the long-term perspective.Conclusions. ocrelizumab can be considered as the main treatment alternative for patients with highly active MS and patients with a high risk of progressive multifocal leukoencephalopathy. However, an additional assessment of the risk caused by rare adverse events is needed.